1991
DOI: 10.3109/09513599109028447
|View full text |Cite
|
Sign up to set email alerts
|

The luteinizing hormone pulsatile secretion: Diurnal excursions in normally cycling and postmenopausal women

Abstract: While numerous investigations have determined characteristics of episodic luteinizing hormone (LH) secretion in women, any diurnal LH rhythmicities during eugonadal and hypogonadal states have not been accurately addressed. Accordingly, blood was sampled at 15-min intervals for 24 h in 45 normally cycling women (16 early follicular (EFP), 14 late follicular (LFP), 15 mid-luteal phase (MLP) women) and in eight postmenopausal women (PMW). Pulse attributes (amplitudes, interpulse intervals) determined in the LH s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 38 publications
0
13
0
1
Order By: Relevance
“…During the course of the experiment, we observe a gradual increase in plasma Lh levels also in the control group. This phenomenon may be explained by diurnal rhythms of Lh as reported in mammals [59,60] and fish [61,62] or may be due to acute stress imposed by the handling and treatments [63]. Kiss1-15 also up-regulates gnrh1 and gpr54-2 mRNA levels in prepubertal fish, although higher levels than Kiss2-12 are needed to obtain the same effect (Fig.…”
Section: Kiss 1 and 2 Regulate Reproduction In Modern Fishmentioning
confidence: 81%
“…During the course of the experiment, we observe a gradual increase in plasma Lh levels also in the control group. This phenomenon may be explained by diurnal rhythms of Lh as reported in mammals [59,60] and fish [61,62] or may be due to acute stress imposed by the handling and treatments [63]. Kiss1-15 also up-regulates gnrh1 and gpr54-2 mRNA levels in prepubertal fish, although higher levels than Kiss2-12 are needed to obtain the same effect (Fig.…”
Section: Kiss 1 and 2 Regulate Reproduction In Modern Fishmentioning
confidence: 81%
“…Moreover, some methods of assessing LH pulse changes may have masked true differences. For instance, although one study described significant diurnal changes of LH pulse frequency in 11 of 14 women in the late follicular phase, cosinor analysis of composite data revealed no significant changes (28).…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies by Loucks and colleagues (15)(16)(17) suggest that late follicular LH pulse frequency slows by 20 -30% during sleep, others have not found nocturnal decreases in LH frequency during the late follicular phase (6,28,29,35). The reasons for discrepancies among these studies are unclear, but possibilities include the use of different LH assays, unfavorable LH sampling frequencies [e.g., every 15 (28,29) or 20 (35) min vs. every 10 min (15-17)], and older methods of pulse detection [e.g., Santen and Bardin method (6,35)]. Methods for assigning LH pulse frequency differed as well, although employed methods were not always clearly reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a 24-hour variation in LH secretion has been reported in postmenopausal women in several studies, with maximal levels observed during the nighttime hours [34]. In contrast, another group reported no consistent 24-hour variation after menopause [35].…”
Section: Femalesmentioning
confidence: 96%